COMPARATIVE STUDY ON ANTIOXIDANT POTENTIAL AND ANTICATARACT ACTIVITY OF CYPERUS ROTUNDUS AND CYAMOPSIS TETRAGONOLOBUS - S. SEEMA; C. N. BHARATHI PRIYA; K. VIJAYALAKSHMI (The Bioscan, 2011)
In this study, the ethanolic extracts of rhizome of Cyperus rotundus and fruits of Cyamopsis tetragonolobus were prepared by successive extraction procedure and subsequently both the extracts were evaluated for its phytoconstituents. Phytochemical tests revealed the presence of phenol, flavonoids, tannins, terpenoids and phlobatannins in both the extracts. Saponin was present only in C. rotundus and cardiac glycoside was present in C. tetragonolobus alone. The extracts were evaluated for its in vitro antioxidant property by 1, 1-diphenyl 2-picryl hydrazyl radical (DPPH) assay, sodium nitroprusside generated nitric oxide (NO) and superoxide anion free radical scavenging methods. The reducing power of the extract was determined by potassium ferricyanide. The anticataract potential of both extracts in glucose-induced cataractogenesis in vitro was studied using lens from Lutjanus campechanus. The lens was subjected to estimation of biochemical parameters and antioxidant enzymes. A rise in malondialdehyde and hydroperoxide was observed in cataract-induced lens as compared to control lens. Decrease in protein, glutathione and vitamin C level was noted in cataractous lens. A significant restoration in superoxide dismutase, catalase and glutathione peroxidase activity was found in the lenses treated with extracts. Both the extracts prevent or delay cataract development by virtue of its antioxidant properties. C. rotundus was found to be more effective in preventing cataract and it may be due to its higher phenol and flavonoid content.